Plasma Membranes Are Subcompartmentalized into a Plethora of Coexisting and Diverse Microdomains in Arabidopsis and Nicotiana benthamiana . Issue 4 (8th April 2014) - Jarsch, Iris K.; Konrad, Sebastian S.A.; Stratil, Thomas F.; Urbanus, Susan L.; Szymanski, Witold; Braun, Pascal; Braun, Karl-Heinz; Ott, Thomas
Abstract : The diversity and dynamics of membrane domains in living plant cells is characterized using imaging-based approaches. Examining the diversity of microdomains that are targeted by members of the large Remorin family revealed that these sites may serve as platforms for interactions between different types of membrane-resident proteins and may contribute to their functions. Abstract: Eukaryotic plasma membranes are highly compartmentalized structures. So far, only a few individual proteins that function in a wide range of cellular processes have been shown to segregate into microdomains. However, the biological roles of most microdomain-associated proteins are unknown. Here, we investigated the heterogeneity of distinct microdomains and the complexity of their coexistence. This diversity was determined in living cells of intact multicellular tissues using 20 different marker proteins from Arabidopsis thaliana, mostly belonging to the Remorin protein family. These proteins associate with microdomains at the cytosolic leaflet of the plasma membrane. We characterized these membrane domains and determined their lateral dynamics by extensive quantitative image analysis. Systematic colocalization experiments with an extended subset of marker proteins tested in 45 different combinations revealed the coexistence of highly distinct membrane domains on individual cell surfaces. These data provide valuable tools to study the lateral segregation of membrane proteins and their biological functions in living plant cells. They also demonstrate that widely used biochemical approaches such as detergent-resistant membranes cannot resolve this biological complexity of membrane compartmentalization in vivo.